Release of Microplastics from Reusable Kitchen Plasticware and Generation of Thermal Potential Toxic Degradation Products in the Oven - Jander, Juri; Hummel, Darius; Stürmer, Sophie; Monteleone, Adrian; Neumaier, Tizian; Broghammer, Felix; Lewin-Kretzschmar, Uta; Brock, Thomas; Knoll, Martin; Fath, Andreas Siegbert (Applied sciences, 2022)
Plastics are one of the most important technical materials at present, yet they are associated with a whole series of environmental problems such as micro-and nanoplastics or their plasticizers, which have become increasingly relevant in recent years. While there are many studies that focus on microplastics (MPs) introduced into the human body through commercially produced food, there are nearly none that consider the MPs we ingest through homemade food made with plastic kitchen utensils such as mixing bowls. To investigate this, samples were obtained by exposing different plastic bowls made of acrylonitrile–butadiene–styrene (ABS), polypropylene (PP), melamine, polyethylene (PE), polystyrene (PS), and styrene–acrylonitrile (SAN), to mechanical stress and then analyzed via infrared spectroscopy. This not only raises the question of whether microplastics are incorporated into foods but also the extent to which the degradation products produced by thermal stress in an oven could play a toxicological role. Degradation products were generated by pyrolysis and analyzed afterwards using gas chromatography mass spectrometry. There were differences in the number of microplastic particles abraded by the different types of plastic, with the most consisting of melamine (898 particles) and the least consisting of low-density polyethylene (331 particles). There were also differences in the number and relevance of the thermal degradation products for the different plastics, so that a human toxicological assessment would have to be evaluated in further work.